Finding Nemo - Computer adventure games (Calabasas Hills, CA : $b THQ, $c c2003, 2003)
Includes 7 different games
Title from disc label
System requirements for Windows: Intel Pentium II 266 MHz processor (Pentium III 400 MHz recommended); 64 MB RAM (128 MB for Windows 2000/XP); 160 MB free hard drive space; Windows 98/2000/Me/XP; DirectX 8.1; 8X CD-ROM drive; video card with minimum 8 MB VRAM; DirectX-compatible display capable of 800x600 resolution and 16-bit color; 16-bit Sound Blaster-compatible sound card; Microsoft-compatible mouse
1
Keywords: Computer adventure games; Fishes -- Computer games -- MPL